2019
DOI: 10.3390/ma12101593
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Grain Orientation Evolution in SnPb/SnAgCu Interconnects Under Electrical Current Stressing at Cryogenic Temperature

Abstract: Electromigration was characterized at the cathode Cu/solder interface—without the effect of Joule heating—by employing scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD) analyses. Rapid (Cux,Ni1−x)6Sn5 intermetallic compound (IMC) growth was observed at the anomalous region at the cathode end due to the effect of current crowding. The abnormal isotropic diffusion and parallel distribution of Pb were characterized in an ultra-low temperature environment in a monocrystalline structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Instead, the study found that the Pb migrated in a parallel path. On the contrary, the Pb rapidly migrated along a specific direction (the c-axis of the Sn) during the electromigration at room temperature [ 75 ]. The different migration routes of the Pb were due to the different crystal structures of the Sn at the two temperatures.…”
Section: Effect Of Sn Grain Orientation On Electromigrationmentioning
confidence: 99%
“…Instead, the study found that the Pb migrated in a parallel path. On the contrary, the Pb rapidly migrated along a specific direction (the c-axis of the Sn) during the electromigration at room temperature [ 75 ]. The different migration routes of the Pb were due to the different crystal structures of the Sn at the two temperatures.…”
Section: Effect Of Sn Grain Orientation On Electromigrationmentioning
confidence: 99%